19 Heterosis Effects on Pre-Weaning Traits in a Multibreed Beef Cattle Herd in Panama. (22nd October 2022) - Gonzalez Murray, Roderick A; Martinez, Pedro Guerra; Vigil, Virginia; Moreno, Edwing; Ramirez, Alexandra; Carreño, Luis; Vargas, Dimas; Lezcano, Endhier; Enns, R Mark; Speidel, Scott E; Thomas, Milton G
Abstract: The aim of this study was to estimate the influence of heterosis and breed percentage on birth weight (BW) and weaning weight (WW) in beef cows in a tropical environment. Data from 900 calves and 2, 843 individuals in the pedigree, from the multibreed herd of the Panama Agricultural Innovation Institute (IDIAP) in Gualaca, Panama were used. The herd was comprised of the following genetic groups and according to their breed percentage: tropical adapted Brahman (BR), Nellore (Ne), Un define Bos indicus (BI), Guaymi Creole (CR), Senepol (SP) Romosinuano (RS); Bos taurus (BT), Simmental (SM), Angus (A), Red Angus (AR), Limousin (LM), Charolais (CH), Wagyu (Wa), and Others (Oth); crossbreeds (cx), Beefmaster (BF), Three cx(F1 x different BT), R1(Backcross BR), R2 (Backcross BT), Composite (combination of at least 4 different breeds with less than 25% of Zebu), Upgrade (87.5% BR 12.5% BT), B1 (62.5% Zebu + 37.5% BT), B2 (62.5% BT + 37.5% Zebu). A bivariate animal model for BW and WW, was utilized to estimate variance components. Contemporary group was defined as year of birth. The effects of sex, birth season, weaning season, and age of dam were included as categorical fixed effects. Weaning age, degree of outcross and breed percentage were included as linear covariates. The estimated regression coefficient for BW on heterosis was not significant (P > 0.05), and for WW was 0.072 ± 0.027 kg (P < 0.05). Lower BW and WW were observed for the Japanese, and B1, while R2 and Upgrade had the highest average (P < 0.05). Heritability for BW was found to be low (0.14 ± 0.06) and moderate for WW (0.26 ± 0.09). The proportion of variation of WW accounted by maternal permanent environment for WW was (0.2 ± 0.09). The estimated genetic correlation between additive genetic BW and WW was 0.63 ± 0.30, while a negative, additive genetic correlation was observed for WW and WW maternal (-0.43 ± 0.37). These results suggested that heterosis had a beneficial influence on WW but limited effect on BW. Additionally, increasing the percentage of Wa, and BR negatively influenced WW measurements in a multibreed beef cattle herd in Panama.